Algoritma Haar Cascade Deteksi WajahMenggunakan Phyton - Dede Erwan; Yovi Apridiansyah; Erwin Dwika Putra; Ujang Juhardi (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2022)
The face is one of the body parts that exist in humans which is often used as a sign of identification between one person and another, so the face can be said to be a unique thing because it has differences. With these differences, faces are often used as a marker of self-identity so that they can be recognized by others. The introduction of this identity is an important thing that is used in various purposes, such as attendance attendance, online exams, banking transactions, online buying and selling, and so on. Even in the development of technology today is increasingly progressing, one of which is facial recognition technology can be used to access security unlocks on smartphones. In this study, face detection can be done using the Haarcascade method. The Haar Cascade algorithm is one of the algorithms used to detect a face. The algorithm is able to detect quickly and in real time an object including a human face. In analyzing face detection using the Haar cascade algorithm, the input image must match what will be detected so that it can detect the face precisely. The light intensity must be sufficient for the face to be detected. The testing process was carried out with a distance of 50 Cm, 80 Cm and 100 Cm with the results of measurements using a successful matrix confussion with a value of 92%.